THE ECONOMIC IMPACT OF PUBLIC-PRIVATE PARTNERSHIPS IN INFRASTRUCTURE DEVELOPMENT: A STUDY OF URBAN INFRASTRUCTURE PROJECTS IN TAMIL NADU - P. Amarjothi (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This study explores the economic impact of Public-Private Partnerships (PPPs) on urban infrastructure development in Tamil Nadu, India. Through an analysis of both quantitative and qualitative data, the research assesses the contribution of PPPs to economic growth, employment generation, community development, and service accessibility. A total of 300 respondents were surveyed, and thematic analysis of interviews with key stakeholders, including government officials, private sector representatives, and community members, was conducted. The findings reveal strong positive correlations between PPP projects and economic indicators such as employment, income generation, and community development. Despite these benefits, challenges such as regulatory delays, financing issues, and community resistance were identified. The study highlights that while PPPs contribute significantly to infrastructure development and economic growth, there is a need for enhanced transparency, risk management, and community engagement to ensure sustainable and inclusive outcomes. This research provides valuable insights into the role of PPPs in urban development and offers recommendations for improving their implementation in Tamil Nadu's infrastructure sector.